Hyaluronic Acid Is an Effective Dermal Filler for Lip Augmentation: A Meta-Analysis - Czumbel, László Márk; Farkasdi, Sándor; Gede, Noémi; Mikó, Alexandra; Csupor, Dezső; Lukács, Anita; Gaál, Valéria; Kiss, Szabolcs; Hegyi, Péter; Varga, Gábor (Frontiers in Surgery, 2021)
Introduction. The lips and the mouth play an indispensable role in vocalization, mastication and face aesthetics. Various noxious factors may alter and destruct the original structure, and appearance of the lips and the anatomical area surrounding the mouth. The application of hyaluronic acid (HA) may serve as a safe method for lip regeneration. Although a number of studies exist for HA effectiveness and safety, its beneficial effect is not well established. Aim. The present meta-analysis and systematic review was performed to investigate the effectiveness of HA on lip augmentation. We also investigated the types and nature of adverse effects (AEs) of HA application. Methods. We reported our meta-analysis in accordance with the PRISMA Statement. PROSPERO protocol registration: CRD42018102899. We performed the systematic literature search in CENTRAL, Embase, and MEDLINE. Randomized controlled trials, cohort studies, case series and case reports were included. The untransformed proportion (random-effects, DerSimonian-Laird method) of responder rate to HA injection was calculated. For treatment related AEs descriptive statistics were used. Results. The systematic literature search yielded 32 eligible records for descriptive statistics and 10 records for quantitative synthesis. The results indicated that the overall estimate of responders (percentage of subjects with increased lip fullness by one point or higher) was 91% (ES=0.91, 95% CI:0.85—0.96) 2 months after injection. The rate of responders was 74% (ES=0.74, 95% CI:0.66—0.82) and 46% (ES=0.46, 95% CI:0.28—0.65) after 6 and 12 months, respectively. We included 1496 participants for estimating the event rates of AEs. The most frequent treatment-related AEs were tenderness (88.8%), injection site swelling (74.3%) and bruising (39.5%). Rare AEs included foreign body granulomas (0.6%), herpes labialis (0.6%) and angioedema (0.3%). Conclusion. Our meta-analysis revealed that lip augmentation with injectable HA is an efficient method for increasing lip fullness for at least up to 6 months after augmentation. Moreover, we found that most AEs of HA treatment were mild or moderate, but a small number of serious adverse effects were also found. In conclusion, further well-designed RCTs are still needed to make the presently available evidence stronger.